Evaluation of primary care attributes at the first level of care in Ayacucho, Peru - Lizana, Magaly (2020)
Objective: To evaluate primary care attributes at the four first level of care centers in Ayacucho, Peru. Methods: a cross-sectional study was carried-out from 5-24 of February, 2018. An interview using the short version of the structured Brazilian Primary Care Assessment Tool translated into Spanish was done. Results: The least qualified attributes were family focus, community orientation and first contact-accessibility, in contrast coordination and first contact-utilization and globality attained the highest qualification. Marked differences were found among the centers with the exception of family focus that was found deficient by all centers. Conclusions: Differences in the attributes were found among the first level centers evaluated.